In silico and empirical evaluation of twelve metabarcoding primer sets for insectivorous diet analyses. Issue 13 (21st May 2020) - Tournayre, Orianne; Leuchtmann, Maxime; Filippi‐Codaccioni, Ondine; Trillat, Marine; Piry, Sylvain; Pontier, Dominique; Charbonnel, Nathalie; Galan, Maxime
Abstract: During the most recent decade, environmental DNA metabarcoding approaches have been both developed and improved to minimize the biological and technical biases in these protocols. However, challenges remain, notably those relating to primer design. In the current study, we comprehensively assessed the performance of ten COI and two 16S primer pairs for eDNA metabarcoding, including novel and previously published primers. We used a combined approach of in silico, in vivo‐mock community (33 arthropod taxa from 16 orders), and guano‐based analyses to identify primer sets that would maximize arthropod detection and taxonomic identification, successfully identify the predator (bat) species, and minimize the time and financial costs of the experiment. We focused on two insectivorous bat species that live together in mixed colonies: the greater horseshoe bat ( Rhinolophus ferrumequinum ) and Geoffroy's bat ( Myotis emarginatus ). We found that primer degeneracy is the main factor that influences arthropod detection in silico and mock community analyses, while amplicon length is critical for the detection of arthropods from degraded DNA samples. Our guano‐based results highlight the importance of detecting and identifying both predator and prey, as guano samples can be contaminated by other insectivorous species. Moreover, we demonstrate that amplifying bat DNA does not reduce the primers' capacity to detect arthropods. We therefore recommend the simultaneous identification of predator and prey. Finally, our results suggest that up to one‐third of prey occurrences may be unreliable and are probably not of primary interest in diet studies, which may decrease the relevance of combining several primer sets instead of using a single efficient one. In conclusion, this study provides a pragmatic framework for eDNA primer selection with respect to scientific and methodological constraints. Abstract : We applied complementary approaches to identify primer characteristics and primer sets that enable to describe the diet of two sympatric bat species, by maximizing arthropod detection and taxonomic identification, while identifying bat species and minimizing labor time and cost. These approaches included in silico investigations and in vivo analyses of mock communities including arthropod taxa from 16 arthropod orders and bat guano samples. We confirm that the level of primer degeneracy is the main factor influencing arthropod detection for in silico and mock community analyses, while the amplicon length is critical for the detection of arthropods from degraded DNA samples. We show that amplifying bat DNA does not affect the primers' capacity to detect arthropods. As such, our results advocate for the need to identify simultaneously predator and arthropod prey, as fecal samples can be contaminated (here by different insectivorous species).